Toward a universal polymeric material for electrode buffer layers in organic and perovskite solar cells and organic light-emitting diodes - Zhang, Qiang; Zharnikov, Michael (Energy & environmental science, 2018)
A novel concept of an electrode buffer layer material, exhibiting either hole transporting or reducing electrode work function (WF) properties, is demonstrated by the example of a polymeric compound PDTON, which can be utilized as a ‘universal’ electrode (either for anode or cathode) buffer layer material. Depending on the composition ratio of acetic acid and ethyl acetate upon dispersing, PDTON forms two kinds of nanospheres, serving as building blocks and defining the morphology and properties of the respective materials, termed as A-PDTON and C-PDTON. These materials are suitable for hole transport (triphenylamine on the surface of A-PDTON nanospheres) and reducing the WF of an electrode due to the formation of a suitable interfacial dipole (C-PDTON), respectively. We demonstrate the versatility and high compatibility of these two types of the same polymer in organic solar cells, organic light-emitting diodes, and perovskite solar cells, exhibiting comparable or even superior performance compared to the standard device architectures.
Gesehen am 31.03.2020